Family Sacrifice: A Theoretical Approach - Sabah Aiche (Social Empowerment Journal, 2021)
The concept of sacrifice used to appear sometimes in some social science literature, but it has become so neglected today that the voices are being raised to "restore" the sacrifice. Similarly, self-sacrifice in the service of family members previously viewed as a high virtue, now is sometimes described as self-defeating and there is not much place for it in an era dominated by individual . In a neoliberal Western culture that promotes individual advancement through competition, it is no surprise that we encounter ourselves as separable subjects stirred to undertake one self-improvement project after another. We have become entangled in discourse of personal opportunity and personal blame, and that what we achieve or fail in is the result of individual efforts. Self-sacrifice and family love rarely play a role in the current family theory, and the absence of the language of sacrifice reduces our understanding of family processes, and from this standpoint the present study came to present a theoretical conception of the concept of family sacrifice where family sacrifice was presented then the most important factors affecting family sacrifice and finally the most important interventions Psychological family sacrifice.